Court-Mandated Treatment Outcomes for Prescribed Opioid Use Disorder: A Gender Based Study - Lucabeche, Viviana Ximena (Journal of drug issues, 2022)
This study provides empirical information suggesting court-mandated treatment may be a more effective treatment pathway for opioid use disorder (OUD). To examine the effects of mandated treatment for prescription opioid users, we consider the differences in discharge completion rates for court-mandated and non-mandated treatment for both males and females. We use the Treatment Episode Data Set-Discharges (TEDS-D) from 2015 to 2017 with 13,239, 14,765, and 15,433 cases, respectively, to study successful completion rates for males and females with OUD. Logistic regression analysis confirms a greater completion rate for mandated treatment episodes. Of all mandated females, 59% completed treatment in each of the 3 years as compared to the 59%, 65%, and 64% of successful completion for mandated males, respectively, from 2015 to 2017. Our results suggest court-mandated treatment pathways are more effective on treatment completion for individuals with OUD, yet treatment completion disparity between sexes increases even when females are mandated.